Unanswered questions in cancer‐associated thrombosis. (25th May 2022) - Sanfilippo, Kristen M.; Moik, Florian; Candeloro, Matteo; Ay, Cihan; Di Nisio, Marcello; Lee, Agnes Y. Y.
Summary: Cancer‐associated venous thromboembolism (VTE) is a leading cause of morbidity and mortality in patients with cancer. Treatment of cancer‐associated VTE comes with a heightened risk of anticoagulant‐related bleeding that differs by choice of anticoagulant as well as by patient‐ and disease‐specific risk factors. Available data from randomized controlled trials and observational studies in cancer‐associated VTE suggest that direct oral anticoagulants are effective, continuing anticoagulation beyond six months is indicated in those with active cancer and that patients who develop 'breakthrough' thrombotic events can be effectively treated. We review the evidence that addresses these key clinical questions and offer pragmatic approaches in individualizing care. While significant investigative efforts over the past decade have made impactful advances, future research is needed to better define the factors that contribute to anticoagulant‐related bleeding and VTE recurrence, in order to aid clinical decision‐making that improves the care of patients with cancer‐associated VTE.